Pemanfaatan Agregat Sungai Pucak Kabupaten Maros Untuk Campuran Laston Lapisan Aus - Yospina Malingga; Robert Mangontan; Alpius (Paulus Civil Engineering Journal, 2021)
The purpose of this test is to determine the aggregate characteristics of the Pucak river as Aus Layer Laston Mixture. So, several series of studies were used, starting from testing aggregates (coarse and fine), asphalt and filler, then making compositions to making samples of Laston Wear Layer. The results of this study are to determine the characteristics of the pavement material using aggregate from the Pucak River Maros Regency to meet the requirements of the 2018 General Bina Marga specification, to be used in road layers. Based on the Conventional Marshall test, the Stability, Meltability (flow), Void In Mix (VIM), Void In Mix Aggregate (VMA), and Foid Filled With Bitumen (FVB) all values obtained meet the General Specifications of Highways 2018. And testing Marshall Immersion in the Aus Layer Laston mixture meets the 2018 Highways General Specifications, where the value of the Marshall Remaining Stability is 94.50 ≥ 90%.